Sintesis Zeolit 4A Dari Abu Limbah Sawit Dengan Variasi Ukuran Partikel Abu Sawit Dan Variasi Volume Natrium Silikat Dengan Natrium Aluminat - Lanie Faradina; Fajril Akbar; Silvia Reni Yenti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Zeolite defines as hydrated aluminosilicate minerals which have 3 dimension framework structures formed of silica and alumina tetrahedral by sharing all the oxygen atoms and content with balanced metal load ions of alkaline or alkaline earth metals. Zeolite 4A is synthetic zeolite which have Na+ cation in balancing up the negative charge. Purpose of this research to get advantage from palm ash as a source of silica as feed for zeolite 4A and studied the influence of the palm ash size and ratio of reactan volume. The variation size of palm ash is 60,100, 200 mesh and unsifted ash. Sythesis of zeolite 4A doing by mixing sodium silicate and sodium aluminate with variaton of volume at 55:45 and 60:40 ml/ml and rate of agitation at 200 rpm. Then the gel formed will be heated in the oven at 80oC for 8 hours and washed until pH neutral. After washing process, sample will be dried at 120oC for 3 hours. Sythesis product analyzed with IR Spectroscopy and Xray Difraction. The best result was got in variation size 100 mesh and volume at 55:45 ml/ml.Keyword: Palm Ash, Xray Difraction, IR Spectroscopy, Zeolite 4A